(untitled) (Research, Society and Development, 2023)
Objective: To analyze the acceptance of generic drugs by consumers and associated factors. Method: This was an integrative literature review with a qualitative approach. Results: From the combination of descriptors, 124 studies were obtained. In an initial evaluation through the abstracts, it was found that 64 were outside the time frame, 21 did not answer the guiding question, therefore, 111 articles were excluded. It is possible to select 13 articles to compose the final sample of this bibliographic review. Conclusion: There was a growing confidence on the part of the population regarding the quality, safety and efficacy of generic medicines, where the role of the pharmacist in guiding users in promoting the rational use of medicines stands out. As for the factors that influence this acceptance, the implementation of the Generics Law was evidenced, linked to the low commercial value, as well as the efficacy, safety and proven quality of generic drugs, resulting from greater dissemination of information and duly trained professionals.